Pendidikan Islam Perspektif Muzayyin Arifin dan Relevansinya Terhadap Pendidikan Islam Kontemporer - Sofi Alawiyah Amini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research is motivated by Muzayyin Arifin's thoughts about Islamic education. According to Muzayyin Arifin, Islamic education is an educational process that covers all aspects of human life, both worldly and hereafter, guided by Islamic teachings. Seeing today's modernity that is developing rapidly, of course Islamic education plays an important role in becoming a stronghold for society to avoid negative things in the midst of today's modernity. The purpose of this study is to find out Muzayyin Arifin's thoughts about Islamic education and their relevance to contemporary Islamic education. This study used descriptive qualitative research, using library research as a type of research. The results of this study indicate that, Muzayyin Arifin is a rational religious figure in the world of Islamic education who has several works that discuss Islamic education. There are several thoughts of Muzayyin Arifin concerning the nature of Islamic education, the goals of Islamic education, the processes and products of Islamic education, the goals of Islamic education and Islamic education methodology.